2016
DOI: 10.1021/acs.jpclett.6b00537
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Molecular Dynamics of P3HT:PCBM Bulk Heterojunction: A Time-of-Flight Quasi-Elastic Neutron Scattering Study

Abstract: The molecular dynamics of organic semiconductor blend layers are likely to affect the optoelectronic properties and the performance of devices such as solar cells. We study the dynamics (5-50 ps) of the poly(3-hexylthiophene) (P3HT): phenyl-C61-butyric acid methyl ester (PCBM) blend by time-of-flight quasi-elastic neutron scattering, at temperatures in the range 250-360 K, thus spanning the glass transition temperature region of the polymer and the operation temperature of an OPV device. The behavior of the QE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 15 publications
(35 reference statements)
3
47
1
Order By: Relevance
“…In a previous study, 12 we probed the local dynamics of a blend of regioregular poly(3-hexylthiophene-2,5-diyl) (P3HT) and Phenyl-C61-butyric acid methyl ester (PCBM) at a has been estimated to be between 10 and 25 wt% by various groups 2,9,13-14 and the model of the microstructure comprising solely a neat polymer and a neat fullerene phase has been ruled out experimentally in the favour of a three phase model with the fullerene being mixed with the polymer in the amorphous domain. 2 Phase separation is not achievable reachable within accessible time scales using fully atomistic MD simulations, thus the signal is reconstructed from the following three phases studied separately: crystalline P3HT, crystalline PCBM and the amorphous mixture leading to an overall PCBM loading of 50 wt%.…”
Section: Toc Graphicsmentioning
confidence: 86%
See 1 more Smart Citation
“…In a previous study, 12 we probed the local dynamics of a blend of regioregular poly(3-hexylthiophene-2,5-diyl) (P3HT) and Phenyl-C61-butyric acid methyl ester (PCBM) at a has been estimated to be between 10 and 25 wt% by various groups 2,9,13-14 and the model of the microstructure comprising solely a neat polymer and a neat fullerene phase has been ruled out experimentally in the favour of a three phase model with the fullerene being mixed with the polymer in the amorphous domain. 2 Phase separation is not achievable reachable within accessible time scales using fully atomistic MD simulations, thus the signal is reconstructed from the following three phases studied separately: crystalline P3HT, crystalline PCBM and the amorphous mixture leading to an overall PCBM loading of 50 wt%.…”
Section: Toc Graphicsmentioning
confidence: 86%
“…All the collection runs were carried out for 50 ns with a time step of 2 fs in NPT ensemble using a The simulation shows that the motions of some degrees of freedoms lie lower in energy than the experimental energy window of the IN6 spectrometer. 12 Thus, these motions are too slow to be resolved by the IN6 spectrometer and so are considered as elastic. Other motions lie higher in energy than the experimental energy window of the spectrometer.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…[19,20] Thegroup used selective deuteration of the P3HT side chains in order to isolate and identify the different motions within their samples.T he results were in agreement with those of Paternó et al already discussed in Section 3.1. [19,20] Thegroup used selective deuteration of the P3HT side chains in order to isolate and identify the different motions within their samples.T he results were in agreement with those of Paternó et al already discussed in Section 3.1.…”
Section: Qens and Organic Electronicsmentioning
confidence: 99%
“…Thestudy of P3HT/PCBM blends was also undertaken by Guilbert et al and reported in two related publications. [19,20] Thegroup used selective deuteration of the P3HT side chains in order to isolate and identify the different motions within their samples.T he results were in agreement with those of Paternó et al already discussed in Section 3.1. In addition to the frustrated P3HT motions,G uilbert and co-workers discovered that the polymer also imparted ap lasticising effect on the PCBM portion of the blend, which was especially apparent above the glass transition temperature of the polymer, [19] across all experimentally accessible timescales (5-50 ps).…”
Section: Qens and Organic Electronicsmentioning
confidence: 99%
See 1 more Smart Citation